Prevalence and Angiographic Outcomes of Rescue Intracranial Stenting in Large Vessel Occlusion Following Stroke Thrombectomy – STRATIS - Hamidreza Saber; Michael T. Froehler; Osama O. Zaidat; Ali Aziz‐Sultan; Richard P. Klucznik; Jeffrey L. Saver; Nerses Sanossian; Frank R. Hellinger; Dileep R. Yavagal; Tom L. Yao; Reza Jahan; Diogo C. Haussen; et al. (Stroke: Vascular and Interventional Neurology)
Background Large vessel occlusion secondary to underlying intracranial atherosclerotic disease (ICAD‐LVO) has an estimated prevalence of 7% to30%. There is a large variation in the use of intracranial rescue stenting in interventional practice. We aimed to characterize the frequency and characteristics of intracranial rescue stenting in a large cohort of endovascular therapy for stroke. Methods The Systematic Evaluation of Patients Treated With Stroke Devices for Acute Ischemic Stroke (STRATIS) angiography core lab adjudicated the location of the occlusion, hyperdense vessel sign on initial imaging, the use of angioplasty and stenting, and imaging outcomes following endovascular therapy. Underlying cause of stroke was categorized into intracranial atherosclerosis, cardioembolic, and other subtypes. Statistical analyses examined the relationship between intracranial rescue stenting and imaging outcomes including intracranial hemorrhage, and arterial reperfusion using expanded Thrombolysis in Cerebral Infarction reperfusion score in patients with ICAD‐LVO. Results Among 978 patients with LVO stroke undergoing endovascular therapy, 91 (9.3%) patients had ICAD‐LVO. Baseline hyperdense vessel sign was observed among 44 (62.7%) with ICAD versus 178 (68.2%) with cardioembolic LVO (P = 0.4). Final successful reperfusion (expanded Thrombolysis in Cerebral Infarction 2b50 or more) was significantly lower among ICAD‐LVO as compared with cardioembolic‐LVO (74.2% versus 87.5%; P = 0.007). Intracranial rescue stenting was used among 14/665 (2.1%) of patients with LVO (5 ICA terminus, 7 M1 middle cerebral artery, 1 M2 middle cerebral artery, 1 proximal basilar artery). Among 14 intracranial rescue stenting cases, 5/70 (7.1%) belonged to the ICAD group, 3/261 (1.1%) cardioembolic group, and 6/334 (1.8%) in other or undetermined group. Successful reperfusion following rescue stenting was achieved in all cases with ICAD‐LVO. Among ICAD‐LVO, the rate of 24 hours symptomatic intracranial hemorrhage was 0% with acute intracranial stenting versus 7.7% in the nonstenting subgroup. Conclusion In STRATIS, nearly 1 of every 11 thrombectomies were performed in patients with underlying ICAD, among whom 7.1% underwent rescue intracranial stenting concomitant with thrombectomy. Acute intracranial stenting as rescue therapy in ICAD‐LVO was associated with favorable angiographic outcomes and low symptomatic hemorrhage rates.